Systematic overview of clinical trials of antiarrhythmic drugs - Shilbayeh, Sirin (1998)
BACKGROUND Arrhythmia is a cardiovascular disorder which can lead to several complications. Over the past decade the introduction of many new drugs has raised concerns about their questionable benefits and cost-effectiveness. Classification of antiarrhythmic drugs has not been fully resolved. Although numerous clinical trials have been conducted, the value of antiarrhythmic drugs in many indications remains controversial. Two meta-analyses of clinical trials addressing the indication of quinidine (Class I) for maintenance of sinus rhythm after cardioversion have suggested high efficacy rates but increased mortality relative to placebo. Several overviews which were conducted to evaluate the impact of antiarrhythmic therapy on improving survival post acute myocardial infarction, have defined a turning point in the management strategy from Class I to Class III drugs, particularly amiodarone and sotalol, due to the unfavourable mortality outcome with the former Class. MAJOR AIMS This thesis was conducted with three major aims: 1) To assess both qualitatively and quantitatively the benefits and risks associated with flecainide (Class Ic), amiodarone (Class III), and sotalol (Class III & II) in treatment of chronic atrial fibrillation, acute medical or surgical supraventricular arrhythmias, and life-threatening ventricular arrhythmias developing post acute myocardial infarction; 2) To produce an overall summary estimate of effectiveness and probabilities of incidence of adverse effects, which can be useful for subsequent incorporation in cost-effectiveness analysis; 3) To validate the usefulness of various therapeutic outcomes implemented by general treatment guidelines. OVERVIEW OF THESIS A meta-analysis was carried out to compare the efficacy and safety of three antiarrhythmic agents (flecainide, sotalol, and amiodarone) in maintaining sinus rhythm after cardioversion of chronic atrial fibrillation. 42 of 119 clinical trials retrieved satisfied the predefined inclusion criteria. Data from 17 amiodarone trials (5 randomised, and 12 uncontrolled), 8 sotalol trials (6 randomised, and 2 nonrandomised), and 19 flecainide trials (8 randomised, 4 nonrandomised controlled, and 6 uncontrolled) were pooled separately after testing for homogeneity of treatment effect across the trials. Although the pooled rate difference in proportion of patients remaining in sinus rhythm between amiodarone and placebo (2 trials) was statistically nonsignificant (RD3mon = 16.1 %, 95% CI = -29.7 to 61.7, P>0.05), the pooled effect compared to Class IA drugs (3 trials) demonstrated significant differences at all time intervals (RDs were 20.5%, 31 %, and 28.8% at 3, 6, and 12 months respectively). Aggregating sotalol efficacy data in randomised or nonrandomised controlled trials has yielded highly significant effect in favour of sotalol as compared to placebo and equal effect as compared to Class IA and Class IC at all time points. Furthermore, comparison of flecainide to placebo or Class IA has revealed a highly superior effect in favour of flecainide. The calculated summary statistics (ORpeto, ORMH, RD, and RR) for the incidence of mortality and pro arrhythmia in the full-exposure group in amiodarone and sotalol trials were not significant, affirming the safety of those two drugs. In flecainide placebo-controlled trials, the ORMH for mortality and proarrhythmia were 1.8 (95% CI, 1.2-2.7, P=0.002), and (95% CI, 4.23-10.6, P<0.00l) respectively, thus indicating low benefit-risk ratio for flecainide as compared to amiodarone. The validity of this meta-analysis was examined by assessment of publication bias using funnel-plots. A funnel-plot of the amiodarone clinical trials displayed the shape of an 'inverted funnel', thus suggesting an evidence of low retrieval bias. However, due to the small sample size identified (18 trials only), a firm conclusion with regard to absence of publication bias could not be drawn.